Fatores de risco para infecções urinárias em pacientes submetidos a cateter vesical de demora em unidade de terapia intensiva de um hospital universitário - CARVALHO, Aidê Teles de (Universidade Federal do Pará, 2018)
Health care-related infection is a major public health grievance that in recent years has contributed to the increase in morbidity and mortality rates, hospital stay and costs. The objective of the research was to analyze risk factors for urinary tract infection associated with the use of indwelling catheters in the Intensive Care Unit (ICU) of a federal university hospital in the north of the country, from 2010 to 2013. A study was conducted exploratory, descriptive, retrospective study with a quantitative approach. They used data from the Hospital Infection Control Commission and the Division of Medical Records and Statistics, records and reporting forms and analyzed the incidence, in addition to risk factors, major microorganisms involved in the etiology of this infection and catheter dwell time bladder of delay. When analyzing the data, it became clear that a total of 48 patients, 60% (29/48) were female. The presence of risk factors such as diabetes mellitus, previous treatment with antibiotics and the catheter dwell time were determining factors of ITU-RC. The microorganism most frequently found in positive urine cultures were Candida spp 47% (16/34), Pseudomonas aeruginosa 12% (4/34), Klebsiella spp 9% (3/34), Escherichia coli 9% (3/34) Acinetobacter 9% (3/34), Enterococcus spp 6% (2/34), Serratia marcense 6% (2/34). The results of this study reinforce the importance of an effective hospitalas infection control program and the involvement of all health professionals who work in intensive care units.